ON THE NEED FOR ESTABLISHMENT OF LOGISTICS CENTERS IN UKRAINE - Muzykina, S. I. (Science and Transport Progress, 2008)
The Western companies consider the lack of logistic powers as the main obstacle for activities in the markets of the Eastern Europe in general andUkrainein particular. The same problem makes our country less attractive for international cargo transit.